Fodor's Italy 2009 - Lombardi, Matthew (New York : Fodor's Travel Publications, 2009)
A guide to visiting Italy, describing choice picks for hotels, restaurants, and attractions in different cities and regions, and including trip planning tips, maps, and photographs.
"Pullout map inside.".
Cover title: Italy 2009.
Includes index.
Young Adult
Keywords: Italy -- Guidebooks; Italy -- Guidebooks